The relationship between lung function and headache risk in middle-aged and older adults: a cross-sectional and longitudinal study - Liuyun Huang; Mingjie Xie; Ling Li; Yuanyuan Qin; Qingjiang Cai; Biheng Feng; Debin Huang (European Journal of Medical Research)
Abstract Background The association between lung function and headache risk remains unclear. This study aims to explore the association between lung function and headache risk through cross-sectional and longitudinal analyses. Methods This study used data from the China Health and Retirement Longitudinal Study (CHARLS) spanning 2015 to 2020 to conduct cross-sectional and longitudinal analyses. The cross-sectional analysis included 10,917 middle-aged and older adults aged ≥ 45 years. For the longitudinal component, 5,194 participants from this cohort who had no history of headache diagnosis in the 2015 cross-sectional survey were followed up until 2020. The cross-sectional association between predicted PEF% and headache was examined using multivariate logistic regression and restricted cubic spline (RCS) analysis. For the longitudinal association, Kaplan–Meier curves, multivariable Cox proportional hazards regression models, and RCS analysis were applied to assess the relationship between baseline predicted PEF% levels and the risk of new-onset headache. Additionally, subgroup analyses were performed to explore the consistency of these associations across different subgroups. Results The results of the multivariate logistic regression analysis showed that the probability of headache decreased with increasing PEF% predicted (P < 0.05); compared with the Q1 group, the Q4 group had a lower probability of experiencing headaches (OR = 0.81, 95% CI 0.68–0.96, P = 0.016). During follow-up, a total of 2,428 people (46.7%) developed new-onset headaches. The results of the multivariable Cox regression analysis showed that an increase in PEF% predicted was a protective factor for the occurrence of headaches, and as PEF% predicted increased, the risk of headaches decreased (P < 0.05); compared with the q1 group, the q4 group had a lower risk of headache (HR = 0.94, 95% CI 0.90–0.97, P < 0.001). Subgroup analysis results showed that gender and PEF% predicted had an interaction effect on headache risk (P = 0.005). Conclusions In middle-aged and elderly people, especially middle-aged and elderly women, improving PEF levels may have potential value in the primary prevention of headaches.